(De)Globalisation and the New Industrial Policy - Vuk, Peter (Naše gospodarstvo/Our economy, 2025)
The processes of economic and political cooperation since the Second World War have stimulated economic growth and improved living standards and prosperity, while intensified economic integration and contributed to a better response to global challenges. Following the 2008 global financial crisis, there is a trend towards deglobalisation or slowbalisation. The article provides a comprehensive literature review and examines data sources on the situation and trends related to the globalisation of the world economy and the rise of industrial policy measures in advanced economies. It was found that the world economy is facing several challenges, including the reshaping of global supply chains, mitigating the effects of economic inequality and climate change, and the rise of economic populism and nationalism. This article consequently provides a comprehensive overview of the literature on globalisation and industrial policy, examining the interplay between deglobalisation processes and industrial policy measures and their increasing prominence in advanced economies.
Keywords: World economy; Industrial policy; Globalisation; Deglobalisation